Regulation of Rad52-dependent replication fork recovery through serine ADP-ribosylation of PolD3 - Richards, F; Llorca-Cardenosa, MJ; Langton, J; Buch-Larson, SC; Shamki, NF; Sharma, AB; Nielsen, ML; Lakin, ND (Springer Nature, 2023)
Although Poly(ADP-ribose)-polymerases (PARPs) are key regulators of genome stability, how site-specific ADP-ribosylation regulates DNA repair is unclear. Here, we describe a novel role for PARP1 and PARP2 in regulating Rad52-dependent replication fork repair to maintain cell viability when homologous recombination is dysfunctional, suppress replication-associated DNA damage, and maintain genome stability. Mechanistically, Mre11 and ATM are required for induction of PARP activity in response to replication stress that in turn promotes break-induced replication (BIR) through assembly of Rad52 at stalled/damaged replication forks. Further, by mapping ADP-ribosylation sites induced upon replication stress, we identify that PolD3 is a target for PARP1/PARP2 and that its site-specific ADP-ribosylation is required for BIR activity, replication fork recovery and genome stability. Overall, these data identify a critical role for Mre11-dependent PARP activation and site-specific ADP-ribosylation in regulating BIR to maintain genome integrity during DNA synthesis.